2020
DOI: 10.15627/jd.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Energy Efficiency of Artificial Lighting Control Systems for Stairwells of Multistory Residential Buildings

Abstract: The aim of the research is to determine the economic and energy efficiency usage of the artificial lighting control systems, with the help of astronomical relays and motion sensors, by various types of light sources for the stairwells (stair landings and staircases) of multistory residential buildings. The analysis of the residents' monthly movement intensity of the 9-story residential buildings through the buildings entrance, doorways, and apartment doors was carried out. The economic and energy efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Evaluation using car headlights demonstrated that the system effectively reduces energy consumption for street lighting. Burmaka et al, (2020) assessed the cost and energy savings of using artificial lighting control systems in residential stairwells. Results showed that combining astronomical relays and motion sensors significantly reduced electricity consumption, with savings ranging from 43.31% to 97.73%, depending on the light source.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation using car headlights demonstrated that the system effectively reduces energy consumption for street lighting. Burmaka et al, (2020) assessed the cost and energy savings of using artificial lighting control systems in residential stairwells. Results showed that combining astronomical relays and motion sensors significantly reduced electricity consumption, with savings ranging from 43.31% to 97.73%, depending on the light source.…”
Section: Introductionmentioning
confidence: 99%
“…The representation of the manual control behaviour is one of the challenges in energy performance simulations. Nowadays, the reported energy savings refer to various baseline scenarios, often making unrealistic assumptions such as lighting that is continuously switched on or ignoring presence of daylight [1,7,12]. In fact, manual control is driven by interactions between circumstances and variables, including residents' occupation, type of room, preferred illuminance levels and degree of fatigue [11].…”
Section: Introductionmentioning
confidence: 99%